Should the U.S. Shut Down Gitmo? (American Journal of Islam and Society, 2006)
This panel discussion, held on 27 June 2006 and sponsored by the Councilon American-Islamic Relations (CAIR), featured James Yee, a 1990 WestPoint graduate and Muslim chaplain assigned to Camp Delta (Guantanamo Bay) and attorney Gene Fidell of Feldesman, Tucker, Leifer, and Fidell, whohas worked on cases involving Guantanamo Bay inmates. The discussiontook place at the Rayburn House Office Building in Washington, DC.After making opening remarks on illegal immigrants and terrorism,Mohammad Nimer (research director, CAIR) introduced Chaplain Yee, whohad served at Camp Delta from November 2002 to September 2003. Whilethere, he experienced the detention center's living conditions and receivedawards and recognition for his service. On 10 September 2003, however, hewas arrested and accused of espionage, aiding the enemy, mutiny, and sedition.Eventually, he was locked up alongside enemy combatants YasserHamdy and Jose Padilla in a naval brig in South Carolina. Later, all chargeswere dropped, including unrelated charges regarding national security.Yee explained his role as advocating for the free exercise of worship. Headvised the camp commander on religious aspects of prison operations andlistened to prisoners’ complaints and concerns, including authorized andunescorted access to the cells. In addition, he observed detainee treatmentand made recommendations. He described two operations: detention operationsrun by military police or guards (e.g., providing them with clothes) andintelligence gathering, which included extracting information. Yee wasassigned to the former group, as the commanding general at the time, MajorGeneral Geoffrey Miller, considered it unethical for the chaplain to be presentduring intelligence gathering operations ...